2005
DOI: 10.1523/jneurosci.2693-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute γ-Secretase Inhibition Improves Contextual Fear Conditioning in the Tg2576 Mouse Model of Alzheimer's Disease

Abstract: Transgenic mice (Tg2576) overexpressing the Swedish mutation of the human amyloid precursor protein display biochemical, pathological, and behavioral markers consistent with many aspects of Alzheimer's disease, including impaired hippocampal function. Impaired, hippocampal-dependent, contextual fear conditioning (CFC) is observed in mice as young as 20 weeks of age. This impairment can be attenuated after treatment before training with the phosphodiesterase-4 inhibitor rolipram (0.1 mg/kg, i.p.). A rolipram-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
149
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(170 citation statements)
references
References 36 publications
(44 reference statements)
18
149
3
Order By: Relevance
“…As demonstrated by ours and others' studies, Tg2576 mice at this age exhibit associative learning and memory impairments in the contextual fear conditioning test (Corcoran et al, 2002;Dineley et al, 2002;Comery et al, 2005). Several lines of evidence support the notion that early cognitive deficits in AD mouse models are triggered by oligomeric assemblies of Aβ rather than plaque-associated Aβ (Cleary et al, 2005b;Selkoe, 2005;Lesne et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As demonstrated by ours and others' studies, Tg2576 mice at this age exhibit associative learning and memory impairments in the contextual fear conditioning test (Corcoran et al, 2002;Dineley et al, 2002;Comery et al, 2005). Several lines of evidence support the notion that early cognitive deficits in AD mouse models are triggered by oligomeric assemblies of Aβ rather than plaque-associated Aβ (Cleary et al, 2005b;Selkoe, 2005;Lesne et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Next, we tested the hypothesis that such CaN inhibition would alleviate the associative learning deficit exhibited by 5 month old Tg2576 mice (Corcoran et al, 2002;Dineley et al, 2002;Comery et al, 2005). Tg2576 mice and their wild type littermates were subjected to 2-pair training in the rodent fear conditioning paradigm.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether this negative effect on dendritic spine density can also be observed in aged WT mice (Lanz et al, 2003) was not analyzed. Together, chronic GSI treatment over 4 consecutive days led to a loss of dendritic spines, whereas acute GSI treatment in previous studies was not found to alter spine density in organotypic hippocampal slices (Kamenetz et al, 2003) or cognition (Comery et al, 2005). We did not analyze whether the spine loss after chronic ␥-secretase inhibition actually affects cognition.…”
Section: Discussionmentioning
confidence: 79%
“…In one study with a ␤-secretase inhibitor, long term treatment improved memory only after several months of treatment (75). In a study of the ␥-secretase inhibitor, there were acute effects on memory function in normal rats (85) and pre-plaque Tg2576 (86), suggesting that drug action may or may not be related to APP, A␤, and AD. It will be of interest to extend our current studies by measuring the progression of memory dysfunction and the levels of multiple A␤ fractions at a range of time points after the initiation of secretase treatment to halt A␤ production.…”
Section: Discussionmentioning
confidence: 99%